Association Between Prebiotic or Probiotic Consumption and Risk of Type 2 Diabetes Mellitus in the General Adult Population - Şefika Tuğba Yangöz; Cansu Koşar Şahin; Hatice Ceylan (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Decrease in microbiota diversity increases risk of diabetes by increasing harmful metabolites and activatinginsulin resistance pathways. Adequate prebiotic and probiotic food consumption may be a potential tool in order to preventtype 2 diabetes.Aim: The aim of the research was to examine at the relationship between probiotic and prebiotic consumption and the risk of type 2 diabetes.Method: A cross-sectional research design was used in this study. Data was obtained from December 2021 and June2022 using Personal Information Form, Assessment of Probiotic and Prebiotic Food Consumption Form, and Finnish Type 2 Diabetes Risk Questionnaire via online survey. General adults were included in this study. Univariate analysis, logistic and multiple linear regression analyses were conducted.Results: Of 401 adults, 51.6% were male and 78.80% were under 45 years of age. 89% of the sample stated they consumed prebiotic-probiotics. Logistic regression analysis showed that prebiotic-probiotic consumption was not a significant predictor of low (p = 0.127), mild (p = 0.381), moderate (p = 0.819), high (p = 0.588) and very high risk of type 2 diabetes (p = 0.998). In the research, linear regression research revealed that there was no meaningful connection between prebiotic-probiotic consumption status and type 2 diabetes risk (β = -0.072; p = 0.151).Conclusion: This research shown that using probiotics or prebiotics did not increase the risk of type 2 diabetes. Thus, more research is required to determine the relation between the usege of probiotics or prebiotics and the risk of type 2 diabetes.